Prevalence and Bacteria Associated with White Band Disease on Acropora sp. from Gili Labak Island Sumenep District Indonesia. Issue 1 (May 2019) - Nugraha, W A; Handoko, A; Insafitri; Effendy, M
Abstract: Coral reefs have many problems including coral diseases. One of the coral diseases that infect Acropora sp. from Gili Labak Island is the White Band Disease (WBD). Their prevalence and bacteria associated with the WBD on Acropora sp. is warranted further investigation. This study aims to determine the disease prevalence and bacteria associated with WBD on Acropora sp. from the Gili Labak Island. The samples were collected from coral infected. The laboratory analysis includes bacterial isolation, DNA extraction, DNA amplification, electrophoresis, sequencing, and phylogenetic analysis. The results showed that the disease prevalences of WBD on Acropora sp. were between 0 to 23%, in which the highest prevalence was found in the site where marine tourism activities and boat mooring occurred. Four bacterial isolates were identified based on morphological features. These four isolates were then analyzed using the Mega 5.2 program and resulted in a complete nucleotide sequence and had similarities to the bacteria present in the Gen Bank through BLAST analysis. The result of BLAST analysis showed that ACWB2A isolate had 99% similarity with Vibrio alginolyticus bacteria; ACWB 6 had 99% similarity with Vibrio owensii; and isolates 5 and 8 had 99% similarity with Pseudoalteromonas rubra bacteria. These are the first record that Pseudoalteromonas rubra bacterium is associated with White Band Disease.